Ante el límite de la representación en el documental: cuerpo filmado, filmado-hablante, filmante, (anti)espectante - Ciancio, María Belén (2017)
This essay re-thinks some of the problems of contemporary documentary filmmaking, including categories such as the figure or author-function (long-debated not only in the field of cinema, but also in the fields of literature and philosophy), the concept of body and spectator, and the problem of representation, in the context of a series of documentaries sometimes considered as post-memory, critical memory, “first person” documentaries, or labyrinthine memory. My hypothesis is that the way in which corporality is modulated in the plot – in which memory and gender are decisive concepts and experiences to the problem of representation – produces not only the specificity in the analysis of certain documentary films, but also and ultimately the way of thinking the place of the body in the modes of production and reproduction in the audio-visual media of the global capitalism.